RELASI BAHASA ARAB DENGAN STRATA SOSIAL MASYARAKAT DAN IMPLIKASINYA TERHADAP KEHIDUPAN SOSIAL, EKONOMI, POLITIK DAN AGAMA (Kajian Sosiolinguistik Pada Masyarakat Tutur Arab Keturunan di Kelurahan Kauman Pekalongan Timur) - Muhandis (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
This study is categorized as sociolinguistic studies and used language variation theory based on social ranks — they are: Akrolek, Basilek, Vulgar, Kolokial — and interactional theory which is a process of interaction that build, maintain, and change certain habits in language and symbols. Listening, speaking, and noting were used to collect data. Unified and apportion analysis method were used to analyze data. The results were: (1) The existence of social rank within the Arab community in Kauman descent was: (a) Cleric group. They were entitled Al-Jufri, Al-Hadad, Al-Ethiopia, Yahya, Shihab, Bawazier and so forth; (b) Masayikh group. They were fam Bafadhal, Bahomaid, Baraja, Baharmi (Baharmus), Bawazir, Basyu'aibn, Bamozaham, Ba'abad, bin Khatib, Bin Zabdah, Basalamah; and (c) Ghabili group. Those who holds Bashir, Baswedan, Sungkar, Abud, Alkatiri, Badjubier, Bafadhal, and so forth. The existence of regional variations of low and high diversity of languages based on social strata, for example ﻗﻬﺎﺭ Gahar (angry), ﺣﺮﻳﻢ Harim (wife), Sir ﺳﺮ (the streets) is a slang vocabulary that includes a low range of languages. If they were categorized in the high language using word ﻏﻀﺒﺎﻥ, ﻗﺮﻳﻨﺔ, and ﺃﻣﺸﻰ. The mention of the word pilgrims for Arabs descent, call ahlul wathan for the Javanese and Chinese descent Baodeh for socially showed no difference in social status between the Javanese and Arab descent on one side, and the Chinese descent on the other side. Regional variations of low and high diversity of languages based on their economic status, usually rich people are often invoked as 'Royyes' (ﺭﻳﺲ) which has the meaning of the aristocracy, including the diversity of languages is low while the high diversity of languages is ﺍجلﻼﻟﺔ ﺻﺎﺣﺐ. Low variation in the range of political language is the word Haromi (ﺣﺮﻣﻰ) which is Arabic kolokial have meaning 'thief' or 'corruptor'. High variety of Arabic word 'corruptor' using the word Mukhtalis (خمﺘﻠﺲ) is not a word Harami and DEFA Rijal (ﺭﺟﺎﻝ ﺩﻓﻊ) is low in Arabic has the meaning of 'builders bribery' and the diversity of languages is high or fushah Rasyi (ﺭﺍﺷﻰ).